Scenes and Tricks by Campos de Carvalho, a Reader of Jarry - Da Rosa, Victor [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2018)
The article brings Alfred Jarry and Campos de Carvalho closer by considering the notion of 'pataphysics, which is defined in Jarry's novel as 'the science of exceptions and imaginary solutions', as well as a series of narrative consequences that such idea implies. The goal is to reread O pucaro bulgaro (1964) through the ways in which the Brazilian author appropriated himself from the imagination of a no place suggested by Jarry in Ubu Rei, and which also reflects in the elements of 'pataphysics. The paper also attempts to clarify the very bases of the temporal drifts that are so striking in Campos de Carvalho's novel, thought of as a sort of time machine. In this way, we try to speculate not only on the impact caused by Jarry's books on the author, but also to point to the singular way in which Campos de Carvalho reworked 'pataphysics', for example, by representing Bulgaria as any other planet , that is, a purely imaginary place.
Keywords: Alfred Jarry; Campos de Carvalho; No Place; 'Patashysics